Phase III Study on Efficacy and Safety of Triple Combination (Exenatide/Metformin/Biphasic Insulin Aspart) Therapy for Type 2 Diabetes Mellitus. (November 2018) - Su, Ke; Lv, Chunmei; Ji, Zongwen; Wang, Yishu; Wang, Haifeng; Bai, Ying; Liu, Yaping
Abstract : Exenatide, metformin (MET), and biphasic insulin aspart 30 (BIA30) have been widely used in the treatment of patients with type 2 diabetes mellitus (T2DM); however, each of these medications has significant adverse effects, which limit their utilization. This study aimed to evaluate the efficacy and safety of triple combination (exenatide/metformin/biphasic insulin aspart) therapy for T2DM. Two hundred patients with poorly controlled T2DM were randomly divided into the low-dose (0.5 μg exenatide, 0.05 U·kg −1 ·d −1 BIA30, and 0.01 g MET twice daily) and normal-dose (2 μg exenatide, 0.2 U·kg −1 ·d −1 BIA30, and 0.05 g MET twice daily) groups for 48 weeks of treatment. Of note, 82 and 90 individuals from the low-dose and normal-dose groups, respectively, completed the study. The levels of adiponectin, C-reactive protein, tumor necrosis factor–α, and resistin were measured. The normal-dose treatment was more effective at lowering hemoglobin A1c levels than the low-dose therapy (HbA1c changes of −2.5 ± 0.19% and −0.8 ± 0.07%, respectively) after 48 weeks. The maximum weight decrease was 0.9 kg in the low-dose group and 4.0 kg in the normal-dose group. The triple combination therapy increased the levels of insulin sensitivity and adiponectin and reduced the levels of C-reactive protein, resistin, and tumor necrosis factor–α. No significant difference in the adverse effects was found between the low-dose and normal-dose groups ( P > 0.05). In conclusion, the investigated triple combination therapy for T2MD is therefore an effective and safe therapeutic strategy.